How do rating agencies score in predicting firm performance - Gunter Löffler; Peter N. Posch (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2007)
We use dynamic panel analysis to examine whether credit rating agencies achieve what they claim to achieve, namely, look into the future when assigning their ratings. We find that Moody's ratings help predict individual financial ratios over a horizon of up to five years. Ratings also predict a multivariate credit score, again over five years. The contribution of ratings appears to be economically significant and robust for different specifications.
Keywords: C33; G20; G33; 330; Credit Ratings; Predictive ability; Dynamic Panel Model; Ratingagentur; Kreditwürdigkeit; Prognose; Statistischer Fehler; Zeit; Panel; USA